Sawtooth pacing with on-axis ICRH modulation in JET-ILW. (6th February 2017) - Lerche, E.; Lennholm, M.; Carvalho, I.S.; Dumortier, P.; Durodie, F.; Van Eester, D.; Graves, J.; Jacquet, P.; Murari, A.
Abstract: A novel technique for sawteeth control in tokamak plasmas using ion-cyclotron resonance heating (ICRH) has been developed in the JET-ILW tokamak. Unlike previous ICRH methods, that explored the destabilization of the internal kink mode when the radio-frequency (RF) wave absorption was placed near the q = 1 surface, the technique presented here consists of stabilizing the sawteeth as fast as possible by applying the ICRH power centrally and subsequently induce a sawtooth crash by switching it off at the appropriate instant. The validation of this method in JET-ILW L-mode discharges, including preliminary tests in H-mode plasmas, is presented.